2021
DOI: 10.1002/pssr.202100411
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Layer‐Ti‐Doped Ga2O3 Thin Films with Tunable Optical Properties and Wide Ultraviolet Optoelectronic Responses

Abstract: Doping and alloying in Ga2O3 to tune electronic and photonic behaviors is still urgent but challenging, whereas Ga2O3 has shown great promise in deep‐ultraviolet (DUV) photodetectors and functional high‐power devices. Herein, atomic‐layer‐Ti‐doped/incorporating Ga2O3 (TGO) thin films with tailored optical properties in the UV region from 200 to 400 nm are described. The Ti content in amorphous TGO thin films is controlled and adjusted up to 11 at% during a plasma‐enhanced atomic layer deposition (PE‐ALD) proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The deposition cycle comprised four stages: TEG pulsing (0.5 s), Ar purging (10.0 s), O plasma processing (18.0 s), and Ar purging (20.0 s). In our previous research, we confirmed that the as-deposited Ga 2 O 3 films were amorphous, as they did not exhibit any X-ray diffraction signals or Raman scattering peaks . Additionally, through transmission electron microscopy (TEM) and spectroscopic ellipsometry (SE), we established a deposition rate of 0.4 Å per cycle .…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…The deposition cycle comprised four stages: TEG pulsing (0.5 s), Ar purging (10.0 s), O plasma processing (18.0 s), and Ar purging (20.0 s). In our previous research, we confirmed that the as-deposited Ga 2 O 3 films were amorphous, as they did not exhibit any X-ray diffraction signals or Raman scattering peaks . Additionally, through transmission electron microscopy (TEM) and spectroscopic ellipsometry (SE), we established a deposition rate of 0.4 Å per cycle .…”
Section: Methodssupporting
confidence: 61%
“…In our previous research, we confirmed that the as-deposited Ga 2 O 3 films were amorphous, as they did not exhibit any X-ray diffraction signals or Raman scattering peaks. 58 Additionally, through transmission electron microscopy (TEM) and spectroscopic ellipsometry (SE), we established a deposition rate of 0.4 Å per cycle. 40 For this experiment, we employed 300 deposition cycles to achieve Ga 2 O 3 films with a thickness of approximately 10 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The materials for constructing UV photodetectors are ultrawide-band gap semiconductors, such as AlGaN, Ga 2 O 3 , and diamond . Ga 2 O 3 is a promising semiconductor material as it possesses an ultrahigh band gap of 4.2–5.2 eV for photodetectors. , However, the practical application of Ga 2 O 3 is still limited by its defects, such as low conductivity and long response time.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ga 2 O 3 is a promising semiconductor material as it possesses an ultrahigh band gap of 4.2−5.2 eV for photodetectors. 7,8 However, the practical application of Ga 2 O 3 is still limited by its defects, such as low conductivity 2 and long response time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Ga 2 O 3 thin film-based solar-blind detector has the most commercial application prospect [6] . The preparation methods of Ga 2 O 3 thin films include metal-organic chemical vapor deposition (MOCVD) [7−9] , molecular beam epitaxy (MBE) [10,11] , atomic layer deposition (ALD) [12−14] , pulse laser deposition (PLD) [15,16] , plasma-enhanced chemical vapor deposition (PECVD) [17] , radio frequency magnetron sputtering (RFMS) [18−21] and so on. The MOCVD, MBE, PLD and ALD methods can strictly control the thickness, composition, and doping concentration for high quality Ga 2 O 3 thin films, but the equipment is complicated or the growth rate is relatively slow with a high production cost.…”
Section: Introductionmentioning
confidence: 99%